2017
DOI: 10.1242/dev.145474
|View full text |Cite
|
Sign up to set email alerts
|

Engrailed acts with Nejire to control decapentaplegic expression in the Drosophila ovarian stem cell niche

Abstract: Homeostasis of adult tissues is maintained by a small number of stem cells, which are sustained by their niches. In the female germline stem cell (GSC) niche, Decapentaplegic (Dpp) is the primary factor that promotes GSC self-renewal. However, the mechanism regulating expression in the niche is largely unknown. Here, we identify a 2.0 kb fragment located in a 5' -regulatory region of the locus containing enhancer activity that drives its expression in the niche. This region is distinct from a previously charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 50 publications
4
38
0
Order By: Relevance
“…We first characterized the adult ovarian expression profile of these two lines. In adult germaria ( Fig S1), we found that the two fusion proteins were detected at high levels in CCs (S1A''',B''' Fig, yellow brackets), sometimes in ECs (S1B Fig, blue brackets) and absent from TF cells (S1A''',B''' Fig, green brackets), and were also detected in prefollicular cells (S1B Fig, orange brackets), reflecting the endogenous dpp expression pattern (Liu et al, 2010Luo et al, 2017;Wang et al, 2008;Xie and Spradling, 2000). For analysis in prepupal ovaries, we used the dpp-nlsGFP transgene since the nuclear Dpp:GFP fusion protein produced was less likely to perturb endogenous Dpp function.…”
Section: The Functions Of Bab1 and Bab2 Are Not Required In Niche Celmentioning
confidence: 77%
See 4 more Smart Citations
“…We first characterized the adult ovarian expression profile of these two lines. In adult germaria ( Fig S1), we found that the two fusion proteins were detected at high levels in CCs (S1A''',B''' Fig, yellow brackets), sometimes in ECs (S1B Fig, blue brackets) and absent from TF cells (S1A''',B''' Fig, green brackets), and were also detected in prefollicular cells (S1B Fig, orange brackets), reflecting the endogenous dpp expression pattern (Liu et al, 2010Luo et al, 2017;Wang et al, 2008;Xie and Spradling, 2000). For analysis in prepupal ovaries, we used the dpp-nlsGFP transgene since the nuclear Dpp:GFP fusion protein produced was less likely to perturb endogenous Dpp function.…”
Section: The Functions Of Bab1 and Bab2 Are Not Required In Niche Celmentioning
confidence: 77%
“…bab regulates Engrailed/Invected accumulation in TF cells, but not in CCs, during larval stages Like the bab genes, engrailed and its paralog invected (en/inv) have also been shown to be involved in proper TF formation (Bolívar et al, 2006). In addition, evidence strongly suggests that En directly controls dpp expression in adult CCs (Luo et al, 2017). Therefore, we addressed whether bab function may act upstream of en/inv in larval stages, and thereby would impact dpp transcriptional regulation indirectly through en/inv.…”
Section: The Functions Of Bab1 and Bab2 Are Not Required In Niche Celmentioning
confidence: 99%
See 3 more Smart Citations